2006
DOI: 10.1016/j.jtcvs.2005.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Autologous skeletal myoblast transplantation in patients with nonacute myocardial infarction: 1-year follow-up

Abstract: In patients with previous myocardial infarction, treatment with skeletal myoblasts in conjunction with coronary artery bypass is safe and feasible and is associated with an increased global and regional left ventricular function, improvement in viability, and perfusion of cardiac tissue and no significant incidence of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(57 citation statements)
references
References 31 publications
0
56
0
1
Order By: Relevance
“…Despite this, most preclinical studies have reported that cell transplantation improves the functional outcome in both ischaemic and nonischaemic cardiomyopathy models [1,10,21]. To account for this discrepancy, it has been hypothesised that the benefit of the procedure is not related to the addition of new donorderived contractile elements but rather to indirect effects like mechanical limitation of remodelling ("girdling" effect) or paracrine actions of the graft on the host tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, most preclinical studies have reported that cell transplantation improves the functional outcome in both ischaemic and nonischaemic cardiomyopathy models [1,10,21]. To account for this discrepancy, it has been hypothesised that the benefit of the procedure is not related to the addition of new donorderived contractile elements but rather to indirect effects like mechanical limitation of remodelling ("girdling" effect) or paracrine actions of the graft on the host tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the specific case of skeletal myoblasts (SM), the results of several preclinical and clinical studies have shown improved functional outcomes following transplantation of these myogenic progenitors into postinfarction scars [9][10][11] (review in Ref. [12]).…”
Section: Introductionmentioning
confidence: 99%
“…19 The other 3 early-phase studies of adjunct-to-coronary artery bypass myoblast injections reported variable results ranging from no 20 to few episodes 21,22 of ventricular arrhythmias. Likewise, the few catheter-based trials have yielded variable data.…”
Section: Clinical Datamentioning
confidence: 99%
“…37 Another possible confounder is the pattern of perfusion, as absent or poor anterograde or collateral filling of the infarct-related artery seems to be a powerful predictor of susceptibility to ventricular arrhythmias. 38 Of note, none of the patients in the MAGIC trial 25 underwent revascularization of the cell-treated segments, which could have increased the risk of arrhythmia, as suggested by the observation that, in the trial conducted by Gavira and associates 20 in which myoblast-transplanted areas were bypassed, there were no report of postoperative arrhythmias. Finally, more recent studies using contrast-enhanced magnetic resonance imaging have shown that the extent of myocardial tissue heterogeneity in the infarct border zone is correlated with ventricular irritability.…”
Section: Nature Of the Underlying Substratementioning
confidence: 99%
“…In patients, although some cases of arrhythmias have been reported, overall, an improvement in the cardiac function together with an increase in the viability and perfusion has been found in most of the clinical trials published so far [79] [76] [80][81][82][83][84][85]. Some studies like that published by Gavira et al have been successful with no cardiac arrhythmia reported after one-year follow-up [80]. In this study, cells were cultured in autologous serum instead of bovine serum, which might be associated with lower inflammation.…”
Section: Clinical Trials Using Skeletal Myoblastsmentioning
confidence: 99%